Low energy consumption dual-ion electrochemical deionization system using NaTi2(PO4)3-AgNPs electrodes - Huang, Yinxi (2021)
Novel desalination technologies with high ion removal capacity and low energy consumption are urgently needed to solve the water scarcity problem. Here we report a novel energy efficient dual-ions electrochemical deionization (DEDI) system with Ag nanoparticles/reduced graphene-oxide (AgNPs/rGO) as chloride ion Faradaic electrode and NaTi2(PO4)3/reduced graphene-oxide (NTP/rGO) as sodium ion Faradaic electrode. During the intercalation process, the sodium ions and chloride ions in the feed solution will be chemically intercalated into NTP/rGO electrode and AgNPs/rGO electrode, respectively. The DEDI system shows a stable and reversible salt removal capacity of 105 mg g−1 for 50 cycles with applied voltage range of −1.2–1.4 V. More importantly, when applying from 0 V to 1.4 V, although the removal capacity is relatively low (35.8 mg g−1), the energy recovery of this system is higher than 30% and the energy consumption is as low as 0.127 Wh g−1. Considering the brackish water used here is 2500 ppm, the energy consumption can be estimated to be 0.254 Wh L−1 for desalination of brackish water to drinkable water (500 ppm). The excellent performance of this DEDI system has made it a promising commercial technology for desalination of brackish water even seawater in the future.